An integrated computational analysis of the structure, dynamics, and ligand binding interactions of the human galectin network - Guardia, Carlos Manuel Alberto (2011)
Galectins, a family of evolutionarily conserved animal lectins, have been shown to modulate signaling processes leading to inflammation, apoptosis, immunoregulation, and angiogenesis through their ability to interact with poly-N-acetyllactosamine-enriched glycoconjugates. To date 16 human galectin carbohydrate recognition domains have been established by sequence analysis and found to be expressed in several tissues. Given the divergent functions of these lectins, it is of vital importance to understand common and differential features in order to search for specific inhibitors of individual members of the human galectin family. In this work we performed an integrated computational analysis of all individual members of the human galectin family. In the first place, we have built homology-based models for galectin-4 and -12 N-terminus, placental protein 13 (PP13) and PP13-like protein for which no experimental structural information is available. We have then performed classical molecular dynamics simulations of the whole 15 members family in free and ligand-bound states to analyze protein and protein–ligand interaction dynamics. Our results show that all galectins adopt the same fold, and the carbohydrate recognition domains are very similar with structural differences located in specific loops. These differences are reflected in the dynamics characteristics, where mobility differences translate into entropy values which significantly influence their ligand affinity. Thus, ligand selectivity appears to be modulated by subtle differences in the monosaccharide binding sites. Taken together, our results may contribute to the understanding, at a molecular level, of the structural and dynamical determinants that distinguish individual human galectins.